Analisa Pengaruh Kecepatan Spindel Dan Kecepatan Makan Terhadap Kekasaran Permukaan Pada Proses Frais Tepi Baja St 37 - Saputra, Ammar Wahyu Agung; Afriany, Reny; Budiman, Arie Yudha (Jurnal Multidisiplin Dehasen (MUDE), 2025)
This study aims to examine the effect of spindle speed and feed rate on surface roughness in the edge milling process using ST 37 steel material. A smooth surface finish is one of the main indicators of machining quality, as it directly relates to wear resistance, friction, and the overall performance of mechanical components. The independent variables in this research are spindle speeds (360 rpm, 580 rpm, and 875 rpm) and feed rates (40 mm/min, 185 mm/min, and 285 mm/min), while the dependent variable is surface roughness (Ra). The machining process was carried out using an Optimum vertical milling machine with a 10 mm diameter HSS endmill cutter. Surface roughness measurements were performed using a Surface Roughness Tester, model SJ-310. The test results indicate that increasing spindle speed tends to reduce surface roughness, resulting in a smoother finish. In contrast, higher feed rates lead to increased surface roughness. The combination of the highest spindle speed (875 rpm) and the lowest feed rate (40 mm/min) produced the smoothest surface. These findings confirm that selecting the appropriate machining parameters significantly affects the final surface quality in the milling process.